FACE MASKS, BETWEEN SOCIAL AND POLITICAL MESSAGES IN COVID-19 PANDEMIC: A SEMIOTIC ANALYSIS - Octavia Chandra Dewi (Metahumaniora, 2022)
In the COVID-19 pandemic, people should wear face masks as medical equipment to stop the spread of the coronavirus. Some people donate and distribute face masks to many other people in social charity events. Unfortunately, these kinds of events are used by some people to do political campaigns while distributing donations. This study conducted a Semiotic analysis to describe and analyze signifiers brought by face masks distributed in a social charity event by a Klaten’s regent that symbolizes social and political messages. Using the concept of ‘rhetoric of the image’ by Barthes (1977), which was dragged into a critical semiotics study, which analyzed the image, colors, and written language on the object observed in a video taken from television news. Political messages are often disguised in social events and publications to gain more supporters for bigger chances to win the election.